2023
DOI: 10.18805/ijar.b-4888
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 Gene Expression Pattern in Peripheral Blood Mononuclear Cells during Different Seasons in Pandharpuri Buffaloes

Abstract: Background: Heat shock protein is one of the most abundant and best characterized heat shock protein family that consists of highly conserved stress proteins. Amongst these heat shock protein family, HSP70 is expressed in response to stress and plays crucial roles in environmental stress tolerance and adaptation. Thermal stress alters the normal body homeostasis and causes severe detrimental effects on production and productivity of animals and impairs growth, immune status of animal. Therefore, the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It might be concluded that the biphasic expression pattern of HSPs helps to protect animals against heat stress. Moreover, it may be used as a biomarker of chronic heat stress in livestock (Bharati et al, 2016;Ambade, 2019). However, expression of HSP70 could be used as a valuable indicator for change in body temperature when it is more than 38.6C and HSP70 is suggested as a reliable biomarker of chronic stress, but just in case of multiple stresses, it's not a reliable indicator of a single stressor (Gaughan et al, 2013).…”
mentioning
confidence: 99%
“…It might be concluded that the biphasic expression pattern of HSPs helps to protect animals against heat stress. Moreover, it may be used as a biomarker of chronic heat stress in livestock (Bharati et al, 2016;Ambade, 2019). However, expression of HSP70 could be used as a valuable indicator for change in body temperature when it is more than 38.6C and HSP70 is suggested as a reliable biomarker of chronic stress, but just in case of multiple stresses, it's not a reliable indicator of a single stressor (Gaughan et al, 2013).…”
mentioning
confidence: 99%